MicroMI: A portable microbiological mobile incubator that uses inexpensive lithium power banks for field microbiology. (October 2021) - Diep, Tai The; Bizley, Samuel; Ray, Partha Pratim; Edwards, Alexander Daniel
Graphical abstract: Abstract: Incubation at controlled temperature is a key step in culture based microbiological tests. Access to culture-based microbiological testing requires access to conventional incubators in a laboratory. Portable incubators allow microbiological testing in the field and in resource-limited settings, and can eliminate the challenge of sample transportation, minimising the chance of sample degradation. Recent studies have reported low-cost portable incubator designs suitable for field or off-grid use, but these either need an external power supply (e.g. mains AC or 12 V DC), or rely on passive heating without thermostatic control. Here we report that small inexpensive uninterruptable power supply (UPS) products manufactured for consumer electronics and powered by lithium-ion battery packs allowing thermostatic temperature control in small portable incubators that can maintain precise temperatures with or without external power. We present an open-source design for a Microbiological Mobile Incubator (MicroMI) in two sizes for field use. The MicroMI is built from simple and widely available components and is easy to set up. The open source design can be customised for different numbers of samples. The smallest and most efficient design uses a vacuum insulated food flask that allows longer operation with smaller, lower capacity UPS. The larger flight case design has space for more samples, but depletes the battery faster. The UPS maintains a typical microbiology incubation temperature for up to 24 h without external power- ideal for typical incubation needed for culture methods. The battery capacity, incubator design, and external ambient temperature all affected duration of operation without requiring external power. We validated the MicroMI by conducting classical microbiological tests using agar petri dishes, slant cultures and dip slides, and biochemical tests. We conclude the MicroMI design allows inexpensive lithium battery products to be used to simplify field microbiology and increase access to vital analytical microbiology testing.